Correction: Immunological detection of pyrazine-2-carboxylic acid for the detection of pyrazinamide resistance in Mycobacterium tuberculosis. - Edgar A Florentini; Noelia Angulo; Robert H Gilman; Roberto Alcántara; Elisa Roncal; Ricardo Antiparra; Emily Toscano; Katherine Vallejos; Daniela E Kirwan; Mirko Zimic; Patricia Sheen (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0241600.].